Extrahepatic Portal Vein Obstruction and Portal Vein Thrombosis in Special Situations: Need for a New Classification - Wani, Zeeshan A. (Saudi J Gastroenterol, 2015)
Extrahepatic portal vein obstruction is a vascular disorder of liver, which results in obstruction and cavernomatous transformation of portal vein with or without the involvement of intrahepatic portal vein, splenic vein, or superior mesenteric vein. Portal vein obstruction due to chronic liver disease, neoplasm, or postsurgery is a separate entity and is not the same as extrahepatic portal vein obstruction. Patients with extrahepatic portal vein obstruction are generally young and belong mostly to Asian countries. It is therefore very important to define portal vein thrombosis as acute or chronic from management point of view. Portal vein thrombosis in certain situations such as liver transplant and postsurgical/liver transplant period is an evolving area and needs extensive research. There is a need for a new classification, which includes all areas of the entity. In the current review, the most recent literature of extrahepatic portal vein obstruction is reviewed and summarized.